ABUNDANCE OF CORAL FISH SPECIES AND THE CONDITION OF CORAL REEFS IN THE WATERS OF THE TIKUS ISLAND, BENGKULU CITY - Paniska, Almaarif; Samiaji, Joko; Thamrin, Thamrin (Asian Journal of Aquatic Sciences, 2020)
Coral reefs are one of the ecosystems that have ecological functions for marine life, one of which is reef fish. Coral fish are marine biota that live in association with coral reefs. This study aims to determine the abundance of reef fish, the condition of coral reefs and the relationship between abundance of reef fish and coral reefs. This research was conducted in June 2019 in the waters of Tikus Island, Bengkulu City. The method used is a survey method. Data collection on reef fish was carried out using the Underwater Visual Census (UVC) method and coral reefs condition data colletion is done using the Line Intercept Transect (LIT) method. The abundance of reef fish found at the study site averages in the abundant category. At station I, an abundance of reef fish was 2,18 ind/m2, at station II it was 4,18 ind/m2, and at station III it was 1,27 ind/m2. While the average condition of coral reefs at the study site is include in the medium category. At station I, the percentage of live coral cover was 39,30% or include in the medium category. At station II, the percentage of live coral cover was 50,94% or include in the good category. And at station III, the percentage of live coral cover was 46,32% or include in the medium category. Coral fish and coral reefs have a fairly close relationship. Reef fish use coral reefs as a place to find food, shelter and spawn or breed.